2015
DOI: 10.11646/zootaxa.3999.2.4
|View full text |Cite
|
Sign up to set email alerts
|

A new species of the genus Odorrana (Amphibia: Ranidae) and the first record of Odorrana bacboensis from China

Abstract: A new species of the genus Odorrana (Amphibia: Ranidae) and the first record of Odorrana bacboensis from China AbstractThe genus Odorrana currently contains at least 56 recognized species that inhabits montane streams in subtropical and tropical Asia. Twenty new species have been described in the last decade, indicating the potential cryptic species diversity of this genus. We collected several specimens of Odorrana species from Southern China from 2007 to 2014, and on the basis of a combined morphological ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
(30 reference statements)
0
6
0
1
Order By: Relevance
“…The new species was also compared with all other Odorrana species on morphology. Comparative morphological data were obtained from literatures for O. absita ( Stuart & Chan-ard, 2005 ), O. amamiensis ( Matsui, 1994 ), O. andersonii ( Boulenger, 1882 ), O. anlungensis ( Hu, Zhao & Liu, 1973 ), O. arunachalensis ( Saikia, Sinha & Kharkongor, 2017 ), O. aureola ( Stuart et al, 2006 ), O. bacboensis ( Bain et al, 2003 ), O. banaorum ( Bain et al, 2003 ), O. bolavensis ( Stuart & Bain, 2005 ), O. cangyuanensis ( Yang, 2008 ), O. chapaensis ( Bourret, 1937 ), O. chloronota ( Günther, 1876 ), O. exiliversabilis (Li et al, 2001 in Fei, Ye & Li, 2001b ), O. fengkaiensis ( Wang et al, 2015 ), O. geminata ( Bain et al, 2009 ), O. gigatympana ( Orlov, Natalia & Cuc, 2006 ), O. grahami ( Boulenger, 1917 ), O. graminea ( Boulenger, 1900 “1899”), O. hainanensis ( Fei, Ye & Li, 2001a ), O. hejiangensis ( Deng & Yu, 1992 ), O. hosii ( Boulenger, 1891 ), O. huanggangensis ( Chen, Zhou & Zheng, 2010a ), O. heatwolei ( Stuart & Bain, 2005 ), O. hmongorum ( Bain et al, 2003 ), O. indeprensa ( Bain & Stuart, 2005 ), O. ishikawae ( Stejneger, 1901 ), O. jingdongensis ( Fei, Ye & Li, 2001a ), O. junlianensis ( Fei & Ye, 2001 in Ye & Fei, 2001 ), O. khalam ( Stuart, Orlov & Chan-ard, 2005 ), O. kuangwuensis (Liu & Hu, 1966 in Hu, Zhao & Liu, 1966 ), O. leporipes ( Werner, 1930 ), O. lipuensis ( Mo et al, 2015 ), O livida ( Blyth, 1856 “1855”), O. macrotympana ( Yang, 2008 ), O. margaretae ( Liu, 1950 ), O. mawphlangensis ( Pi...…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The new species was also compared with all other Odorrana species on morphology. Comparative morphological data were obtained from literatures for O. absita ( Stuart & Chan-ard, 2005 ), O. amamiensis ( Matsui, 1994 ), O. andersonii ( Boulenger, 1882 ), O. anlungensis ( Hu, Zhao & Liu, 1973 ), O. arunachalensis ( Saikia, Sinha & Kharkongor, 2017 ), O. aureola ( Stuart et al, 2006 ), O. bacboensis ( Bain et al, 2003 ), O. banaorum ( Bain et al, 2003 ), O. bolavensis ( Stuart & Bain, 2005 ), O. cangyuanensis ( Yang, 2008 ), O. chapaensis ( Bourret, 1937 ), O. chloronota ( Günther, 1876 ), O. exiliversabilis (Li et al, 2001 in Fei, Ye & Li, 2001b ), O. fengkaiensis ( Wang et al, 2015 ), O. geminata ( Bain et al, 2009 ), O. gigatympana ( Orlov, Natalia & Cuc, 2006 ), O. grahami ( Boulenger, 1917 ), O. graminea ( Boulenger, 1900 “1899”), O. hainanensis ( Fei, Ye & Li, 2001a ), O. hejiangensis ( Deng & Yu, 1992 ), O. hosii ( Boulenger, 1891 ), O. huanggangensis ( Chen, Zhou & Zheng, 2010a ), O. heatwolei ( Stuart & Bain, 2005 ), O. hmongorum ( Bain et al, 2003 ), O. indeprensa ( Bain & Stuart, 2005 ), O. ishikawae ( Stejneger, 1901 ), O. jingdongensis ( Fei, Ye & Li, 2001a ), O. junlianensis ( Fei & Ye, 2001 in Ye & Fei, 2001 ), O. khalam ( Stuart, Orlov & Chan-ard, 2005 ), O. kuangwuensis (Liu & Hu, 1966 in Hu, Zhao & Liu, 1966 ), O. leporipes ( Werner, 1930 ), O. lipuensis ( Mo et al, 2015 ), O livida ( Blyth, 1856 “1855”), O. macrotympana ( Yang, 2008 ), O. margaretae ( Liu, 1950 ), O. mawphlangensis ( Pi...…”
Section: Methodsmentioning
confidence: 99%
“…The genus currently contains 58 recognized species ( Frost, 2018 ). Noticeably, in the last decade, 13 species have been described ( Li, Lu & Rao, 2008 ; Tran, Orlov & Nguyen, 2008 ; Yang, 2008 ; Bain et al, 2009 ; Chen, Zhou & Zheng, 2010a , 2010b ; Kuramoto et al, 2011 ; Mo et al, 2015 ; Wang et al, 2015 ; Pham et al, 2016 ; Saikia, Sinha & Kharkongor, 2017 ). This indicated that the species diversity has been underestimated and more discoveries were obligatory in the genus.…”
Section: Introductionmentioning
confidence: 99%
“…Serta dilakukan pengukuran morfometri meliputi 19 karakter dan 22 karakter turunan morfometri (diperoleh dari rasio karakter morfometri dibandingkan dengan persenan SVL (R: %SVL)). Pengukuran menggunakan jangka sorong digital dengan ketelitian 0.1 atau 0.01 mm (Wang et al, 2015). Ilustrasi pengukuran mengacu pada gambar pengukuran milik Matsui (1984), yang disesuaikan dengan data yang dibutuhkan.…”
Section: Identifikasi Dan Pengukuran Morfometriunclassified
“…We compared the morphological characters between the new species and its congeners, based on literature values from the following species: Odorrana absita , O. amamiensis (Matsui, 1994), O. andersonii (Boulenger, 1882), O. anlungensis (Hu et al, 1973), O. aureola (Stuart et al, 2006), O. bacboensis (Bain et al, 2003), O. banaorum (Bain et al, 2003), O. bolavensis , O. cangyuanensis (Yang, 2008), O. chapaensis (Bourret, 1937), O. chloronota (Günther, 1876;Che et al 2020), O. exiliversabilis (Fei et al, 2001b), O. fengkaiensis (Wang et al, 2015), O. geminata (Bain et al, 2009), O. gigatympana (Orlov et al, 2006), O. grahami (Boulenger, 1917), O. graminea (Boulenger, 1900), O. hainanensis (Fei et al, 2001a), O. hejiangensis (Deng & Yu, 1992), O. hosii (Boulenger, 1891), O. huanggangensis (Chen et al, 2010a), O. indeprensa , O. ishikawae (Stejneger, 1901), O. jingdongensis (Fei et al, 2001a), O. junlianensis , O. khalam , O. kuangwuensis (Hu et al, 1966), O. kweichowensis (Li et al, 2018a), O. leporipes (Werner, 1930), O. lipuensis (Mo et al, 2015), O. livida (Blyth, 1856), O. lungshengensis (Liu & Hu, 1962), O. macrotympana (Yang, 2008), O. margaretae (Liu, 1950), O. mawphlangensis (Pillai & Chanda, 1977), O. monjerai (Matsui & Jaafar, 2006), O. morafkai (Bain et al, 2003), O. mutschmanni (Pham et al, 2016), O. nanjiangensis (Fei et al, 2007b), O. narina (Stejneg...…”
Section: Morphological Analysismentioning
confidence: 99%
“…Most of the species inhabit mountain streams at elevations of 200-2000 m and can also be found on rocks or branches near the riverbed (Fei et al 2009a;Frost 2020). Seven species from the genus Odorrana have recently been described using both molecular and morphological analyses (Chen et al 2010a, b;Kuramoto et al 2011;Mo et al 2015;Wang et al 2015;Pham et al 2016;Li et al 2018a). The phylogeny and diversity of Odorrana and the systematic status of taxa within the genus have been debated by taxonomists (Frost et al 2006;Che et al 2007;Fei et al 2009a;Kurabayashi et al 2010;Chen et al 2013;Li et al 2015).…”
Section: Introductionmentioning
confidence: 99%